Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2013
DOI: 10.1145/2470654.2466439
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the use of circles in social networks to support independence of individuals with autism

Abstract: Building social support networks is crucial both for lessindependent individuals with autism and for their primary caregivers. In this paper, we describe a four-week exploratory study of a social network service (SNS) that allows young adults with autism to garner support from their family and friends. We explore the unique benefits and challenges of using SNSs to mediate requests for help or advice. In particular, we examine the extent to which specialized features of an SNS can engage users in communicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…OzCHI 2017, Nov 28 -Dec 1, Brisbane, Australia Human -Nature independence for people with Autism Spectrum Conditions [26]. There is also potential here to harness the educational potential of CCBT and to apply this to the problem of stigmatisation towards those with mental health conditions.…”
Section: Long Papersmentioning
confidence: 99%
“…OzCHI 2017, Nov 28 -Dec 1, Brisbane, Australia Human -Nature independence for people with Autism Spectrum Conditions [26]. There is also potential here to harness the educational potential of CCBT and to apply this to the problem of stigmatisation towards those with mental health conditions.…”
Section: Long Papersmentioning
confidence: 99%
“…Studies of online communities conclude that they can provide those who have low self-esteem and limited social networks with informational and emotional support and social companionship [7]. A notable example of computer-mediated social support includes a cross-platform social networking site that links young adults on the autism spectrum with an online circle composed of family, close friends, relatives, and a few selected acquaintances [15]. Despite the benefits of the social media technologies, users with autism experience specific barriers to adopting them due to their difficulties in understanding social norms and managing trusted and healthy online interpersonal relationships [7].…”
Section: A the Use Of Social Media For Individuals With Autismmentioning
confidence: 99%
“…Among the discussion boards presented in Table 1, we excluded discussion boards that were website-specific (1, 2), those mainly used by family and friends of individuals on the spectrum (5) or researchers (6), and one for amusement (15). Thus, we focused on ten discussion boards (3,4,7,8,9,10,11,12,13,14) in which the forum users discuss their everyday experiences, concerns, and challenges.…”
Section: B Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a more recent study considered the use of a supportive social network aiming to provide young adults and adolescents with ASD the opportunity to gain support from a group of family and friends, instead of over-relying on one caregiver. The idea was to use circles (a feature in social networks that combines a group of people interested in a particular topic, or people with a common social connection) in order to seek information and advice, and build independence [24]. These studies showed that including social networks in assistive technologies could bring their benefits to the life of an individual with ASD.…”
Section: Social Technologies and Asdmentioning
confidence: 99%